Ovarian cancer stem cells: What progress have we made?. (February 2019) - Al-Alem, Linah F.; Pandya, Unnati M.; Baker, Andrew T.; Bellio, Chiara; Zarrella, Bianca D.; Clark, Justin; DiGloria, Celeste M.; Rueda, Bo R.
Abstract: Ovarian cancer (OvCa) is the most lethal gynecological malignancy in the United States primarily due to lack of a reliable early diagnostic, high incidence of chemo-resistant recurrent disease as well as profuse tumor heterogeneity. Cancer stem cells (CSCs) continue to gain attention, as they are known to resist chemotherapy, self-renew and re-populate the bulk tumor with undifferentiated and differentiated cells. Moreover, CSCs appear to readily adapt to environmental, immunologic and pharmacologic cues. The plasticity and ability to inactivate or activate signaling pathways promoting their longevity has been, and continues to be, the challenge faced in developing successful CSC targeted therapies. Identifying and understanding unique ovarian CSC markers and the pathways they utilize could reveal new therapeutic opportunities that may offer alternative adjuvant treatment options. Herein, we will discuss the current state of ovarian CSC characterization, their contribution to disease resistance, recurrence and shed light on clinical trials that may target the CSC population.